(untitled) (Ameghiniana, 2014)
The purple clam Amiantis purpurata (Lamarck) is a warm-temperate species which inhabits the shallow waters from Espiritu Santo (Brazil) to northern Patagonia. It is understood to be one of the few survivors of the middle–late Miocene faunal turnover which was characterized by the appearance of new taxa, most of them living today along the Argentinean coast. In order to study the biogeographical history of A. purpurata, a detailed review of its records was carried out. The oldest record of A. purpurata comes from the late Miocene of Uruguay, and it appears that A. purpurata survived because its wide thermal tolerance range allowed larvae to migrate from Uruguay to the south, where they settled on the southern coast of the province of Buenos Aires and the San Matías Gulf. In addition, the characteristics of this gulf would have fostered the development and settlement of the larvae, thus giving rise to the most abundant southern population during the Pleistocene. At the end of the Pleistocene, A. purpurata also survived the Last Glacial Maximum and, once in the Holocene, the A. purpurata population at the San Matías Gulf became isolated, also representing the most abundant southern population of this species. In its brief Neogene geological history, Amiantis purpurata followed main global, regional and local events; thus it can be considered as an environmental indicator for this period.